(untitled) (Academicia Globe: Inderscience Research, 2023)
The formation of a competitive specialist in the modern educational space is possible only with the introduction and inclusion in the educational process of problem- and methodically-oriented innovations that meet the provisions of general innovation processes reflected in programs and concepts.